Upaya Optimalisasi Pengelolaan Simpan Pinjam Melalui Perancangan Sistem Informasi Manajemen di PT. BPR Arisma - Tyas Silvi Ariyani; Ilham Perdana (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Savings and credits are primary activities of PT. BPR Arismentari Ayu (Arisma). However, the management of data and information of savings and credit has not been integrated, which causes problems such as the difficulty of finding information and the loss of information due to missing files. A tool for the better management of savings and credit can be integrated and optimized. The purpose of this study is to optimize the business process savings and credit. The type of research is applied research. The data analysis technique employed was a qualitative approach to data sources derived from primary and secondary data. Sampling was conducted with purposive sampling technique, and the validity test of the data was triangulation. The research began with an analysis of current business processes to identify the needs and problem that existed. Furthermore, the analysis of the results are converted into information system design with Unified Modeling Language tool. In order to understand the user petrified design, the user interface was made as an information system. The last step was the design test of information systems using validating requirement. The information system is expected to improve the quality of management of savings and credit in PT. BPR Arisma. Keywords: Savings and Credit Information Systems, UML, System Design, Waterfall.